PENGARUH CELEBRITY ENDORSEMENT TERHADAP PURCHASE INTENTION DENGAN MEDIASI BRAND IMAGE DAN MODERASI NEGATIVE PUBLICITY - Mulyana, Helmi; Hurriyati, Ratih; Kurniawan, Asep; Widjajanta, Bambang (Image : Jurnal Riset Manajemen, 2022)
The existence of industrial technology 4.0 plays a big role in aspects of human life. One of them is the increasing role of the internet in daily activities to find product/service information and social media to promote it. The low public interest in buying indicates that the competitiveness of Indonesian local cosmetic products is still lacking. The purpose of this study was to determine the description and influence of the celebrity endorser, purchase intention, and brand image variables. This research is descriptive verification with a quantitative approach. The research sample was 100 female respondents. The sampling technique used is purposive sampling. The results showed that the celebrity endorser was in the fairly strong category, the brand image in the strong category, purchase intention in the fairly high category. Data analysis shows that there is a significant positive effect of the celebrity endorser, purchase intention, and brand image variables either directly or indirectly. The role of brand image in mediating the influence of celebrity endorsement on purchase intention shows that entrepreneurs of local cosmetic products must be able to manage and provide strategies for the sustainability of local cosmetic products. It aims to attract attention/attraction so that consumer buying interest increases.